Rahaat – A Web Application Based Donation Platform For Unused/Near To Exprity Medicine - Singhal, Radhika; Goel, Amita; Nidhi Sengar; Bahl, Vasudha (International Journal of Computer Sciences and Engineering, 2022)
Medicine is a major part of healthcare system and availability of these medicine is a task which all government struggle with, to tackle this selling and buying of medicine was introduced in Indian Market. Online marketing is growing at a great pace and with growth in online marketing more and more online pharmacies are getting in the business. Other than this this industry frequently faces the issue of shortage and wastage of medicine and to tackle this problem an idea could be developed. Online medicine trade is worldwide popular due to the cost cutting it offer and easiness. Though online pharma chains provide everything which include prescribed drugs to machines such as bp monitor, glucometer, etc. India’s health sector is expanding for both online and offline supply stores, both are working together to expands their profit. Scarcity of resuscitative medicines have been turned up in most of country around world. Medicines scarcity cause risks for patient well-being and being as a consequence of no-medication, under-medication and possible medicine errors from attempts to substitute missing medicine. While medicine scarcity is a not something new, they have been climbing alarmingly in recent years. Accessible stats from various healthcare facilities and local non governmental organizations specify that products in shortage include many regularly used medicines such as antibiotics, tb(tuberculosis) medicines, cardiovascular(heart related) medicines and many more